The Role of Social Media in Shaping the Learning Behavior and Social Interactions of Middle School Students - Sapto Widodo; Sigit Haryanto; Djalal Fuadi (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the role of social media in shaping the learning behavior and social interactions of junior high school students. The phenomenon of high social media use among adolescents has prompted the need for an in-depth study of its influence on the learning process and social relations in schools. This study used a qualitative approach with a case study design, involving students and teachers of SMP Negeri 1 Kebakkramat as informants. Data were collected through in-depth interviews and analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data presentation, and conclusion drawing. The results show that social media, particularly TikTok, WhatsApp, and Instagram, have become a routine part of students' lives. However, their utilization in learning remains low because students primarily use them for entertainment. The positive impact of social media is seen in easy access to information and accelerated communication, while the dominant negative impacts include distraction, decreased learning focus, and potential conflict in social interactions. The study also found that school policies regarding social media use are still advisory in nature and therefore unable to optimally direct students' digital behavior. This study confirms that social media plays a dual role as a learning and social space, but digital literacy and more systematic supervision are needed so that its use brings more benefits to students.